Calculation of the spatial flow in the francis high-head turbine using the CFD software package - Krupa, Y. S. (Національний технічний університет "Харківський політехнічний інститут", 2021)
At present, the development of software packages for calculating computational fluid dynamics problems has reached a high level of efficiency, accuracy and flexibility, with their help it is possible to solve the most diverse and complex problems. All modern software packages for computational fluid dynamics solve the problems of continuum mechanics using models based on the Navier-Stokes equations. These models are based on three conservation equations: conservation of mass, conservation of momentum and conservation of energy. A numerical simulation of the spatial flow of a high-head radial-axial hydraulic turbine Fr 310 was carried out for two variants of the flow path – with an runner with 15 blades (modification 1) and with 17 blades (modification 2), using the OpenFOAM software package. The OpenFOAM software package is one of the most used products designed to solve fluid dynamics problems and is distributed under a free GPL license (General Purpose License). The process of solving the set hydrodynamic problems using the CFD (Computational fluid dynamics) software package includes the following stages: creating a three-dimensional model of the object under consideration using a computer-aided design system; construction of a computational grid with the required parameters; selection of a mathematical model that most accurately describes the working process in the flow parts of hydraulic machines; selection of a suitable turbulence model; setting boundary conditions. A visualization of the results of a numerical study of two modifications of the Fr 310-V-100 hydraulic turbine is presented. A method for calculating hydraulic losses in the flow path of a hydraulic turbine is presented. The analysis of the results of numerical simulation was performed. This analysis showed that the modification of a hydraulic turbine with a runner with 15 blades is better in terms of efficiency than the modification with 17 blades. Comparison of the two modifications was carried out exceptionally by the values of the hydraulic efficiency of the hydraulic turbine.

В даний час розвиток пакетів прикладних програм для розрахунку задач обчислювальної гідроаеродинаміки досяг високого рівня ефективності, точності і гнучкості, з їх допомогою можна вирішувати самі різноманітні та складні задачі. Всі сучасні пакети програм обчислювальної гідроаеродинаміки вирішують завдання механіки суцільного середовища, використовуючи моделі, побудовані на основі рівнянь Нав'є-Стокса. В основу цих моделей входять три рівняння збереження: збереження маси, збереження імпульсу і збереження енергії. Було проведено чисельне моделювання просторового потоку високонапірної радіально-осьової гідротурбіни РО310 для двох варіантів проточної частини – с робочим колесом, що має 15 лопатей (модифікація 1) та з 17 лопатями (модифікація 2), з використанням пакета прикладних програм OpenFOAM. Програмний комплекс OpenFOAM є одним з найбільш використовуваних продуктів, призначених для вирішення завдань гідродинаміки, що розповсюджуються за вільною ліцензією GPL (General Purpose License). Процес вирішення поставлених гідродинамічних задач за допомогою програмного комплексу CFD (Computational Fluid Dynamics) включає в себе наступні етапи: створення тривимірної моделі розглянутого об'єкта за допомогою системи автоматичного проектування; побудова розрахункової сітки з необхідними параметрами; вибір математичної моделі, яка найточніше описує робочий процес в проточних частинах гідромашин; вибір відповідної моделі турбулентності; завдання граничних умов. Приведено візуалізацію результатів чисельного дослідження двох модифікацій гідротурбіни РО 310-В-100. Представлено методику розрахунку гідравлічних втрат в проточній частині гідротурбіни. Виконано аналіз результатів чисельного моделювання. Даний аналіз показав, що модифікація гідротурбіни з робочим колесом, що має 15 лопатей краща по значенню ККД, ніж модифікація з 17 лопатями. Порівняння двох модифікацій проводилося виключно по значенням гідравлічного ККД гідротурбіни.
Розрахунок просторової течії у високонапірній радіально-осьовій гідротурбіні з використанням програмного пакету CFD
Keywords: hydraulic machines; runner; flow path; efficiency; mathematical model; spatial flow; гідравлічні машини; робоче колесо; проточна частина; коефіцієнт корисної дії; математична модель; просторова течія